Vertical distribution of meiofauna in Banate Bay, Iloilo. - Tancinco, Cielo D.
The study was conducted in the inshore and offshore stations in Banate Bay, Iloilo, West Central Philippines to evaluate the vertical distribution of meiofauna. Field sampling was done on October 13, 2014, a day after the Typhoon Ompong exited the PAR. A total of 18 taxa was identified. The overall mean density recorded was 71.86 ind.? cm-2 which proves to be comparable with previous studies similarly conducted in soft bottoms, such as the Visayan Sea. The top 5 most abundant taxa were the nematodes which comprised 80.40% of the average density in both stations followed by rotifers (5.92%), ostracods (3.71%), polychaetes (2.88%) and harpaticoids (1.61%) altogether comprising 94.52% of the total meiofaunal assemblage. Meiofaunal density was higher in the offshore station (112.52 ind. ? cm-2) compared to the inshore station (31.19 ind. ? cm-2) which was attributed to a lesser degree of sediment disturbance and predominance of silt/clay which hold a greater amount of organic matter (3.46%). Highest meiofaunal density was observed in the surface layers in both stations and declined with depth in the sediment. Nematodes, rotifers, ostracods and polychaetes showed a wider vertical distribution within the sediment compared to harpacticoids which were strictly restricted in the surface layers. In this study, sediment type and oxygen availability governed the vertical distribution of meiofauna while organic matter content proved to be relevant to inshore-offshore distribution of meiofauna